Organizational Support of the Management Control Process in Enterprises with State Participation - Irina V. MINAKOVA; Tatyana N. BUKREEVA; Yuri V. BUKHVOSTOV; Elena V. ALEKSANDROVA; Irina G. KUZMICHEVA (Communications of International Proceedings, 2020)
The study has concluded the importance of complex tools to ensure a management control process at enterprises with state participation. The tools have been divided into two groups, basic tools and operational tools. In particular, the basic tools create the necessary management, financial and legal basis for enterprise’s activities. The operational tools provide effective implementation of the goals and objectives designated by the management at the division level, as well as during direct business operations. As a result, it was created a multi-level system of the main tools for organizational support of management control at enterprises with state participation. The system allows getting a comprehensive idea of the functional purpose of various tools, adjusting the organizational processes. It also increases the responsibility of the executive management for the development and effective implementation of advanced management control system.
Keywords: Management Control; Basic Tools of Management Control; Operational Tools of Management Control; Enterprises with State Participation.